PERANCANGAN MEDIA PEMBELAJARAN TENTANG SUMBER AIR UNTUK ANAK USIA DINI YANG BERLANDASKAN DANU KERTI - I Nyoman Agus Suarya Putra; Dwi Novitasari; Mega Dewi Setyawati; Ni Wayan Wardani (Jurnal Manajemen dan Teknologi Informasi, 2023)
Danu Kerti is an effort to preserve freshwater sources on land such as springs, lakes, rivers, and other springs. Springs are also very important for human life because the availability of clean water is very influential on daily human needs. Water is very important for people’s lives in Bali, even as a means of religious ceremonies. So it is very necessary to socialize about protecting water among the community because it is seen from the current condition of water in Bali which is very concerning which causes water pollution due to garbage and waste. Planting characters to care more about the environment, especially how to protect water, how to give thanks for water water can be used for daily needs such as drinking, bathing, and others, especially since early and through videos. From the results obtained after the children watched this learning video, there was a very good development of understanding about water source and their benefits and this media can also be recommended as an early childhood learning material.